If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -10 = 3x + 5 Reorder the terms: -10 + 6x = 3x + 5 Reorder the terms: -10 + 6x = 5 + 3x Solving -10 + 6x = 5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -10 + 6x + -3x = 5 + 3x + -3x Combine like terms: 6x + -3x = 3x -10 + 3x = 5 + 3x + -3x Combine like terms: 3x + -3x = 0 -10 + 3x = 5 + 0 -10 + 3x = 5 Add '10' to each side of the equation. -10 + 10 + 3x = 5 + 10 Combine like terms: -10 + 10 = 0 0 + 3x = 5 + 10 3x = 5 + 10 Combine like terms: 5 + 10 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| 42y-7=31 | | 54=4w+2w | | 90×2/3 | | M^2+56=15m | | 54=4w | | x-3=-2+3 | | 2*x+3=5*x+17 | | 5(n-1)=55 | | 3x+5.4=(-6.3) | | 8x+y=240 | | 5y-17=-2 | | 5x/5y | | 10+11y+3y^2=0 | | 8-x=-2x+16 | | 6x+9=-6x-81 | | 2x^2+15x-2=0 | | a=17-b | | f(11)=2(11)+4 | | N/3-8=16 | | 8x+9y=96 | | f(11)=2x+4 | | (3^×)(9^2x)=1^3/9 | | y=0.25x+8 | | 5x+20+2x+11=115 | | 14n+3(n+5)=117 | | x^1/4(2x^3/4-x^1/4) | | (5v-3)(5v-2)=0 | | 100+2x+15-9x=5-7x+22-11x | | (1/3x)*(1/3x) | | T/8=2/9 | | 7a+12b=155c | | V/4-9=7 |